2017
DOI: 10.20517/2394-5079.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of emergency and interval hepatectomy for ruptured resectable hepatocellular carcinoma: a single tertiary referral centre experience

Abstract: How to cite this article: Fung AKY, Chong CCN, Lee KF, Wong J, Cheung YS, Fong AKW, Lai PBS. Outcomes of emergency and interval hepatectomy for ruptured resectable hepatocellular carcinoma: a single tertiary referral centre experience. Hepatoma Res 2017;3:196-204. Aim: The short and long term outcomes of patients who underwent emergency and interval hepatectomy for ruptured and resectable hepatocellular carcinoma (HCC) were analysed. Methods: The data of patients with ruptured HCC presenting between April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Peritoneal recurrence was found only in 16.7% of patients in this study and this was comparable to previous studies which reported a rate between 11 -40% with median time to recurrence being 6 -11 months. [14][15][16][17][18] Ruptured HCC and time-to-surgery were the two most common deciding factors for peritoneal recurrence, however, there is some supportive and contradictive evidence regarding this. 14,15,19,20 Most ruptured HCC patients usually presented poor liver function and were excluded from liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal recurrence was found only in 16.7% of patients in this study and this was comparable to previous studies which reported a rate between 11 -40% with median time to recurrence being 6 -11 months. [14][15][16][17][18] Ruptured HCC and time-to-surgery were the two most common deciding factors for peritoneal recurrence, however, there is some supportive and contradictive evidence regarding this. 14,15,19,20 Most ruptured HCC patients usually presented poor liver function and were excluded from liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of developing HCC is significantly higher in the oral nucleos(t)ide analoguescomplete responder group compared with the inactive CHB group, regardless of the presence of baseline liver cirrhosis [4] , indicating that continuous active inflammation in liver facilitates the development of HCC. Although surgical technologies for the treatment of liver cancer have been improved, postoperative prognosis remains to be precisely evaluated [5][6][7] . Active inflammation on chronic inflammation background, as reflected by an Ishak hepatic inflammation score (> 6), a higher neutrophil-tolymphocyte ratio (> 5), and a higher C-reactive protein in sera (> 0.3 mg/dL), etc., also indicate a poor postoperative prognosis such as postoperative recurrence and shorter recurrence-free survival in HBV-related HCC (HBV-HCC) patients [8,9] .…”
mentioning
confidence: 99%